Refractive errors and academic performance in elementary school (Colombia Medica, 1989)
A total of 832 students between the ages of 6 and 14 years of public primary school in Cali, Colombia, were screened with the Snellen test. Children with abnormal refraction were sent to the optometrist for final assessment. A vision defect rate of 16.8% was found, and a highly significant association between a visual defect and the low-efficiency school. Only 5% have correction with glasses.